The Effect of Nitric Oxide Microinjection in Nucleus Accumbens Shell on Morphine Withdrawal Signs in Male Rats - V Sheibani; Gh Sepehri; F Baghaiee; R Farazifard (Journal of Kerman University of Medical Sciences, 2005)
Introduction: This study was performed to evaluate the effects of intra-nucleus accumbens shell microinjection of Larginine (NO precursor) and L-NAME (nitric oxide synthase (NOS) inhibitor) on morphine withdrawal signs in male rats. Method: Rats were anaesthetized with a combination of ketamine and xylazine, and placed in stereotaxic apparatus, and a guide cannula was inserted into nucleus accumbens (Nacc) shell, (1.7 mm Anterior to bregma, 0.8 mm bilaterally to bregma and 7.1 mm depth from skull surface). Morphine dependency was induced by subcutaneous administration of morphine (10-20 mg/kg for 5 days), and morphine withdrawal signs were precipitated by naloxone administration (4 mg/kg/ip). Rats received either single or repeated microinjections of saline, L-arginine or L-NAME into Nacc shell during the scheduled periods for 5 days. In Sham group, bilateral canulla was inserted into Nacc shell , but no drug was microinjected, and in saline group only normal saline was injected into Nacc shell in the same way as the experimental groups during the scheduled periods.Control group was intact. Results: The results of this study showed no significant difference between control and saline treated groups in the expression of morphine withdrawal signs. Single dose microinjection of L-NAME / L-arginine, just prior to the last injection of morphine, had no effect on morphine withdrawal signs, but repeated microinjection of L-arginine / LNAME decreased jumping, rearing and weight loss (only in L-NAME group), as compared to control rats. Conclusion: The obtained results indicate that NO injection in Nacc shell may be involved in some of morphine withdrawal signs